Health and Wellbeing in an Outdoor and Adventure Sports Context - John Allan; Ashley Hardwell; Chris Kay; Suzanne Peacock; Melissa Hart; Michelle Dillon; Eric Brymer (MDPI AG, 2020)
Outdoor and adventure sports (OAS) have been linked to positive health and wellbeing outcomes. This Special Edition brings together cutting-edge research and thought on the implications of this link. An analysis of the papers in this Special Edition reveals important insights into (i) the diverse and powerful outcomes derived from adventure experiences, (ii) how adventure experiences facilitate these outcomes, (iii) how best to design outdoor and adventure experiences. The evidence in this edition indicates a need for a more systematic approach to the inclusion of OAS as important to good health and wellbeing. OAS should be included as part of education, health, policy and planning.